Trade openness, institutional quality and economic development in Asean countries - Pham, Thi Trang (2017)
This dissertation studies the individual impacts of trade openness and institutional quality as well as their interactive effects on economic development in Southeast Asian countries. The research confirms many theoretical reviews and empirical findings that both trade openness and good institutional quality positively affect income. Moreover, there exists an interaction between trade openness and the quality of institutions to affect economic development, though the signs of effects can be positive and significant or not depending on distinct good governance indicators, which are proxies for institutional quality. The results propose some implications for ASEAN countries under its regional and global integration in trade as well as governance policies so as to continue to achieve higher economic development.